Participatory Research with Romanian Roma Immigrants Living in Polish Settlements: Methodology, Results and Barriers - Czarnota, Katarzyna (Participatory Social Work: Research, Practice, Education, 2019)
Systemic segregation and economic exclusion of Romanian Roma immigrants in Poland, starting in the 1990s, has deprived this group from the right to work, health care, welfare system and adequate housing. Roma encampments built from recycled materials represent the most radical forms of collective response to the problem of access to housing. A group consisting of sociologists and activists conducted the first Polish sociological intervention studies with this community living in Polish encampments. The final report has been created in cooperation with Roma people. These studies show problems which this community is facing, making it impossible for the authorities to further ignore the presence of these people in Poland. The result of this research has been used to support social change in this community, and continues to support claims made to local authorities to change their policy. In this chapter I focus on the analysis of existing forms of cooperation with this community and the challenges faced by people who want to enter into the emancipatory forms of cooperation with Roma immigrants, presenting the possible fields of cooperation and obstacles.